Consequences of soil attributes on the productivity and eucalypt drought response in two climate types in Brazil - Silva, Vinicius Evangelista [UNESP]; Buzetti, Salatier [UNESP]; Laclau, Jean-Paul; Montanari, Rafael [UNESP]; Panosso, Alan Rodrigo [UNESP]; Moreira Dias, Sharlles Christian; Silva, Joao Flavio da (Centro Pesquisas Florestais, Ufsm, 2020)
The present study aimed to evaluate the correlations between productivity and eucalyptus drought (DR) response between soil attributes in two distinct climatic types in Brazil. For this, 24 experiments were installed in Brazil with four common clones in all the experiments to obtain strong edaphoclimatic contrasts, and, thus, to measure the productivity and the response to drought and to describe its relationship with the attributes of the soils. Two climatic groups were evaluated: Wet (precipitation rate: evapotranspiration between 1.0 to 2.5) and Sub-Humid (precipitation rate: evapotranspiration between 0.5 to 1.0). The attributes of the evaluated soils were: Sand, Silt, Clay, organic matter (O.M.), cation exchange capacity (CEC). For sites located in the wet climate class, CVWB correlated negatively with O.M. and clay, and positively with the sand. For DR, the correlations were observed for the Sub-Humid climate for the CEC and Sand variables, and for the Humid climate, no correlations were observed between the attributes of soils with DR.
Keywords: Climate; Edaphoclimatic groups; Tolerance to forest aridity; Soil quality